A NOVEL APPROACH TO CERULOPLASMIN STABILITY: PUTTING PROTEASE INHIBITORS INTO PRACTICE (British Journal of Global Ecology and Sustainable Development, 2024)
Ceruloplasmin (CP) is a multi-subunit protein that is central to copper metabolism in the human body [7; Р. 722–732]. This protein not only performs a transport function by delivering copper to tissues, but also serves as an important marker of inflammatory processes and pathologies associated with impaired copper metabolism [3; Р. 6904–6910, 8; Р. 27–36]. Additional studies have shown that plasma ceruloplasmin levels can be altered in a variety of diseases, including hereditary and autoimmune disorders [5; Р. 887–905]. This emphasises the critical importance of accurate quantification of its levels in clinical practice, as these data can have a significant impact on diagnosis and subsequent treatment [1; Р. 1–18].